Compositional Differences in Dissolved Organic Matter Between Arctic Cold Seeps Versus Non-Seep Sites at the Svalbard Continental Margin and the Barents Sea - Sert, Muhammed Fatih; D’Andrilli, Juliana; Gründger, Friederike; Niemann, Helge; Granskog, Mats A.; Pavlov, Alexey K.; Ferré, Bénédicte; Silyakova, Anna (Frontiers in Earth Science, 2020)
Dissociating gas hydrates, submerged permafrost, and gas bearing sediments release methane to the water column from a multitude of seeps in the Arctic Ocean. The seeping methane dissolves and supports the growth of aerobic methane oxidizing bacteria (MOB), but the effect of seepage and seep related biogeochemical processes on water column dissolved organic matter (DOM) dynamics is not well constrained. We compared dissolved methane, nutrients, chlorophyll, and particulate matter concentrations and methane oxidation (MOx) rates from previously characterized seep and non-seep areas at the continental margin of Svalbard and the Barents Sea in May and June 2017. DOM molecular composition was determined by Electrospray Ionization Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR MS). We found that the chemical diversity of DOM was 3 to 5 % higher and constituted more protein- and lipid-like composition near methane seeps when compared to non-seep areas. Distributions of nutrients, chlorophyll, and particulate matter however, were essentially governed by the water column hydrography and primary production. We surmise that the organic intermediates directly derived from seepage or indirectly from seep-related biogeochemical processes, e.g. MOx, modifies the composition of DOM leading to distinct DOM molecular-level signatures in the water column at cold seeps.